2022
DOI: 10.1097/meg.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cannabis consumption in patients with inflammatory bowel disease: prevalence, pattern of consumption and impact on the disease

Abstract: Objectives of the study There is little guidance regarding the impact of alcohol and cannabis on the clinical course of inflammatory bowel disease. The aim of this study was to assess the prevalence, sociodemographic characteristics and impact of alcohol and cannabis use on the clinical course of the disease. Methods We performed an analysis of prospectively collected data within the Swiss Inflammatory Bowel Disease Cohort Study with yearly follow-ups and substance-specific questionnaires. We analyzed the prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As indicated by Casey et al [ 36 ], the effect of ethanol on the gut may be potentially associated with the development of inflammatory bowel disease and impairment of the gut barrier function and permeability [ 37 ], along with its proinflammatory actions, including decreasing T-cell activity [ 38 ] and increasing TNF-α, interleukin-1, and interleukin-6 levels [ 39 ]. At the same time, in ulcerative colitis patients, it was observed that low-to-moderate alcohol drinking compared with heavy drinking was associated with less extensive disease [ 40 ]. Finally, the consumption of alcoholic beverages is known to interfere with the metabolism of colitis-specific medications, which may lead to a loss of their therapeutic effect or to an increased risk of side effects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Casey et al [ 36 ], the effect of ethanol on the gut may be potentially associated with the development of inflammatory bowel disease and impairment of the gut barrier function and permeability [ 37 ], along with its proinflammatory actions, including decreasing T-cell activity [ 38 ] and increasing TNF-α, interleukin-1, and interleukin-6 levels [ 39 ]. At the same time, in ulcerative colitis patients, it was observed that low-to-moderate alcohol drinking compared with heavy drinking was associated with less extensive disease [ 40 ]. Finally, the consumption of alcoholic beverages is known to interfere with the metabolism of colitis-specific medications, which may lead to a loss of their therapeutic effect or to an increased risk of side effects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this field, the specific alcohol interaction with the central nervous system via the gut-brain axis remains unclear, but studies propose that alcohol-triggered leaky gut may result in a systemic inflammation affecting neuronal function [ 122 ]. This condition could contribute to symptoms like anxiety during alcohol withdrawal [ 123 ], and even moderate alcohol consumption can lead to increased gut motility and disrupt the balance of gut microbiota, potentially developing symptoms like diarrhea, bloating, and abdominal pain [ 124 , 125 ].…”
Section: Which Foods and Food Patterns Can Cause Intolerance?mentioning
confidence: 99%
“…In patients with CD, the relative statistical weight of smoking was larger than the relative weight of the genetic variants presented in the previous section[ 1 ]. Besides, cannabis is frequently used as a symptomatic treatment by patients with CD involving the ileum and is associated with tobacco[ 117 ]. Regarding cannabis use, in a double-blind, randomized, placebo-controlled trial, cannabis oil induced clinical improvement without any endoscopic change[ 118 ].…”
Section: Environmental Factorsmentioning
confidence: 99%